PROBLEMS OF REDUCING THE CRIMINALIZATION OF INVESTMENT ACTIVITIES OF JOINT-STOCK COMPANIES AND THEIR SOLUTIONS - Kuvatova Oliya Sheraliyevna (American Journals Publishing, 2023)
The article analyzes the relationship between the development of the shadow economy and investment activities, studies the reasons of the criminalization of investment activities of joint-stock companies, companies and organizations. Control mechanisms which are proposed to reduce the shadow component of the economy and develop investment activities.
Keywords: investment activity, economic growth, direct investment, financial investment, legal economy, criminalization, pressure of taxation, capital flight, phenomenon of criminalization , criminal economy, corruption.